Quality Policy for MI Graduates to Produce Hafiz Al Quran Graduates at MIS Lumbang and MIN Rakha Amuntai South Kalimantan/ Kebijakan Mutu Lulusan MI untuk Menghasilkan Lulusan Hafiz Al Quran di MIS Lumbang dan MIN Rakha Amuntai Kalimantan Selatan - Anwar Rahman; Sutrisno Sutrisno (Edulab : Majalah Ilmiah Laboratorium Pendidikan, 2021)
The purpose of this study is to explain the reasons and implementation of policies in MIS Lumbang and MIN Rakha Amuntai implementing the graduate policy of students in hafiz Al Quran. The method used in this study is a qualitatively described method using Miles and Huberman model analysis and for data validation using data triangulation. The results obtained to state that MIS Al Islamiyah Lumbang has a reason for the policy of graduates of hafiz Al Quran because the quality of graduates of hafiz Al Quran will show the characteristics of madrasah, providing students' provision in society. While MIN Rakha has a reason with the quality of hafiz al Quran graduates can improve the quality of madrasahs and will be one of the attractions of Madrasah. The implementation of the quality policy of graduates of hafiz Al Qur'an in MIS Al Islamiah Lumbang village with the stage of dividing the activity time with learning hours, providing Quran material and selected prayers and others. While at MIN Rakha Amuntai the management of the quality policy of graduates of hafiz Al Qura'an with the stages of holding material books and memorization guides, and giving program time for one hour. Abstrak Tujuan dari penelitian ini adalah menjelaskan alasan dan pelaksanaan kebijakan di MIS Lumbang dan MIN Rakha Amuntai melaksanakan kebijakan lulusan siswa mejadi hafiz Al Quran. Metode yang digunakan pada penelitian ini adalah metode kualitatif diskriptif dengan menggunakan analisis model Miles dan Huberman dan untuk validasi data menggunakan triangulasi data. Hasil yang diperoleh menyatakan bahwa MIS Al Islamiyah Lumbang memiliki alasan untuk kebijakan lulusan hafiz Al Quran karena mutu lulusan hafiz Al Quran akan menunjukkan ciri khas madrasah dan memberikan bekal siswa dalam bermasyarakat. Sedangkan MIN Rakha memiliki alasan dengan mutu lulusan hafiz Al Quran dapat meningkatkan kualitas madrasah dan akan menjadi salah satu daya tarik dari Madrasah. Pemberlakuan kebijakan mutu lulusan hafiz Al Qur’an di MIS Al Islamiah Lumbang dengan tahapan membagi waktu kegiatan dengan jam pembelajaran, memberikan materi Al Quran dan doa-doa pilihan serta yang lainnya. Sedangkan MIN Rakha Amuntai merelialisasikannya dengan diadakannya buku materi dan panduan menghafal, serta memberikan waktu program selama satu jam.